Design, development and reliability analysis of a four-quadrant electromagnet power supply - Varshney S.; Koli M.; Borage M.; Tiwari S.; Thakurta A.C. (My University, 2025)
The paper deals with design, development and reliability prediction of ±10V, ±10A four-quadrant switch mode power supply. One of the application of this power supply is as a corrector electromagnet power supply in particle accelerators. In this power supply, topology used is a full bridge dc-dc chopper with PWM using unipolar voltage switching operating at 50 kHz. The main features of this supply is its ability to reduce the magnitude of output voltage ripple and increasing the frequency of output ripple thus reducing the size of filter and improved switch utilization factor. Another part of this paper predicts the reliability of this power supply using the procedures followed by MIL-HDBK 217F and various areas are suggested to improve the reliability of this power supply. This power supply attained a peak efficiency as high as 81% and predicts mean time between failures of 614084 hours at 40°C. © 2014 IEEE.